PERBANDINGAN RESISTENSI CANDIDA ALBICANS DAN CANDIDA NON ALBICANS TERHADAP FLUKONAZOL DAN NISTATIN (Kajian pada bilasan orofaring penderita Human Immunodeficiency Virus di RSUP DR. Sardjito, Yogyakarta) - , NUR FITRI ASTUTI, dr. Satiti Retno Pudjiati, Sp.KK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Oropharyngeal candidiasis is the most common opportunistic infection that found among HIV-AIDS patients. Candida albicans had been shifted by C. non albicans as a major cause of oropharyngeal candidiasis in HIV-AIDS patients. Nystatin is the first line therapy in Indonesia to oropharyngeal candidiasis in HIV-AIDS patients. The use of nystatin and fluconazole as treatments for oropharyngeal candidiasis among HIV-AIDS patients are equal in daily practice. Some researches have already showed increasing resistance of Candida sp to fluconazole. There is no studies about resistance comparison of C.albicans, C. non-albicans and Candida sp to fluconazole and nystatin in Indonesia. This study was performed to determine resistance of C.albicans, C. non-albicans and Candida sp to fluconazole and nystatin in oropharyngeal rinse with HIV. This is a cross sectional study. The sample was taken from oropharyngeal rinse of HIV/AIDS patients using 0.9% NaCl solution for 60 seconds. Culture is used an agar CHROM while resistance test used disc diffusion method. The analysis statistic used a chi-square test with significance values p< 0,05. As many as 76 oropharyngeal rinse sample from HIV patients, the growing of Candida sp were 50 (65,8%). The number of species in a culture as a single species was 58%. From 50 sample with the growth of Candida sp, we identified 76 isolates. The number of single species and multiple species are 58% and 42%. Candida sp were grown consisted of 34 (44.74%) C. albicans and 42 (55.26%) C. non albicans. Candida glabrata (22.37%) is the most C.non albicans which were found. Resistance of C. albicans and C.non albicans to fluconazole were 41.18% and 57.14%, while resistance to nystatin were 2.95% and 7.14%. There are no significant differences between resistance of C.albicans and C.non albicans to nystatin (p = 0,0391). There are significant differences between resistance C.albicans, C.non albicans and Candida sp to fluconazole and nystatin (p = 0.000) There are no significant differences between resistance of C.albicans and C.non albicans to nystatin. Resistance of C. albicans, C. non-albicans and Candida sp to flukonazol are higher than nystatin from oropharyngeal rinse taken from HIV-AIDS patients in Dr. Sardjito Hospital, Yogyakarta.